Drink of Immortality : Essays on Distillation and Alcohol Use in Ancient India - Jha, D.N. (Brill | Manohar Publishers & Distributors, 2020)
This collection contains ten articles, the first four of them dealing with the antiquity of distillation process in India which is central to the manufacture of alcohol. Written from different points of view they reflect the lack of unanimity among scholars and throw light on an important aspect of technology. The remaining six articles discuss the evidence of alcohol use in ancient India. Drawing on textual evidence from religious and secular literature, they unravel the lesser known aspects of life of ancient Indians and amply demonstrate how alcohol consumption influenced religion and art. They emphasize that neither the ancient Indians nor their gods and goddesses were abstemious teetotalers: evidence is plentiful to indicate that they were more bon vivant than we can imagine or give them credit for.